Diabetes in old age - Sinclair, Alan (Alan J.); Dunning, Trisha; Manas, Leocadio Rodriguez; Munshi, Medha N. (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley-Blackwell, 2017)
'Diabetes in Old Age was the first textbook dedicated specifically to the issue of diabetes in older people, and is accepted internationally as the market-leading contribution to the literature. Comprehensive in its content and with a strong evidence-based focus throughout, the entire range of issues surrounding diabetes and its many complications are covered, and all with a clear focus on how they relate specifically to the elderly patient. In addition, areas unique to the elderly such as management of falls, diabetes and frailty, and diabetes and cognitive dysfunction form a key cornerstone of the book. In every chapter, best practice points and key learning outcomes are provided, as well as published evidence bases for each major conclusion. Diabetes in Old Age 4e will be an essential read for diabetologists of all levels, geriatricians, and all other health professionals involved in providing diabetes care to older people. All health professionals and social care professionals who are directly involved in the care of older people with diabetes will gain benefit from this textbook. This applies to doctors and nurses and allied health professionals who have acquired professional qualifications and are licensed to practice by their regulatory body. All clinicians in training grades will also acquire new learning experiences and valuable insightful information which will assist them in their study processes'--Provided by publisher.
'Only textbook to give different approaches to optimising diabetes care in the community, primary care and secondary care health care arenas for older people'--Provided by publisher.
Includes bibliographical references and index.
Print version record.
Keywords: Diabetes in old age; Diabetes mellitus; Aged; Electronic books